Analiza socjometryczna w ocenie grupy społecznej i budowaniu zespołu sportowego = Sociometry in the assessment of social group and sport team building - Ussorowska, Anna; Mieszkowska, Monika; Graczyk, Marek (Journal of Education, Health and Sport, 2016)
Ussorowska Anna, Mieszkowska Monika. Graczyk Marek. Analiza socjometryczna w ocenie grupy społecznej i budowaniu zespołu sportowego = Sociometry in the assessment of social group and sport team building. Journal of Education, Health and Sport. 2016;6(8):719-733. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.62023 http://ojs.ukw.edu.pl/index.php/johs/article/view/3842 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016. Review article ANALIZA SOCJOMETRYCZNA W OCENIE GRUPY SPOŁECZNEJ I BUDOWANIU ZESPOŁU SPORTOWEGO Sociometry in the assessment of social group and sport team building Anna Ussorowskaa, Monika Mieszkowskab, Marek GraczykC a Uniwersytet Gdański, Wydział Nauk Społecznych, ul. Bażyńskiego 4, 80-952 Gdańsk, Polska b Uniwersytet Medyczny im. Karola Marcinkowskiego w Poznaniu, ul. Fredry 10, 61-701 Poznań, Polska c Akademia Wychowania Fizycznego i Sportu im. Jędrzeja Śniadeckiego, ul. Kazimierza Górskiego 1, 80-336 Gdańsk, Polska Key words: physical activity, sociometry, social relations development Słowa kluczowe: aktywność fizyczna, socjometria, budowanie relacji społecznych Streszczenie Socjometria jako metoda badawcza jest powszechnie wykorzystywana zarówno w socjologii jak i psychologii społecznej, głównie do oceny i pomiaru struktur władzy, współpracy i komunikacji pomiędzy jednostkami danej populacji oraz spoistości określonych grup społecznych. Głównym celem takiego działania jest ocena kierunku i siły stosunków przyciągania i odrzucania, które występują między przedstawicielami danych grup. W sporcie, a zwłaszcza dyscyplinach drużynowych, które odpowiadają założeniom małych grup społecznych czynnik relacji międzyosobowych jest szczególnie istotny w budowaniu drużyny, a co za tym idzie w tworzeniu odpowiednich warunków do osiągania wysokich wyników sportowych. Znajomość nieformalnej struktury społecznej zespołu sportowego może okazać się cennym źródłem informacji, które świadomy trener jest w stanie odpowiednio wykorzystać. Posiadając wiedzę na temat czynników kształtujących relacje interpersonalne, można na nie świadomie oddziaływać w celu korekty i eliminacji zachowań niepożądanych. Ponadto dzięki świadomemu kształtowaniu i monitorowaniu właściwych postaw w drużynie trener jest w stanie istotnie poprawić sytuację interpersonalną pojedynczego zawodnika, a co za tym idzie znacząco wpływać na ogólną atmosferę panująca wewnątrz drużyny, co jak dowodzą liczne badania naukowego bezpośrednio koreluje z efektywnością działań drużyny i osiąganiu wysokich wyników w rywalizacji. Abstract Sociometry as a research method has been widely used both in sociology and social psychology, especially for assessment and measurement of power structures, cooperation and communication between units of the small population and the cohesion of specific social groups. The main purpose of such action is to evaluate the direction and forces of “attraction and rejection” relations that exist between the representatives of such groups. In sports, especially team disciplines (that correspond to the assumptions of small social groups) interpersonal relationship factor is very important in building of a team structure and thus that to create the right conditions to achieve high goals. Knowledge of informal social structure of sport team can be a valuable source of information for conscious coach to use. With knowledge about the factors influencing on interpersonal relations, it is possible to affect on them and eliminate unwanted behaviors. Moreover, thanks to the conscious shaping and monitoring the proper attitudes in team trainer is able to improve the interpersonal situation of a single player. By doing this the general atmosphere within the team will improve which has been found in numerous studies to correlate with in the effectiveness of team activities in achieving high goals.